Synthesis of 2-Aryl Benzothiazoles via K2S2O8-Mediated Oxidative Condensation of Benzothiazoles with Benzylamines - Yang, Zhiyong; Wang, Anwei; Chen, Xiang; Gui, Qingwen; Liu, Jidan; Tan, Ze; Wang, Hua; Shi, Ji-Cheng (Synlett, 2013)
A novel way to synthesize 2-arylbenzothiazoles is described. Reactions of benzothiazoles with diverse benzylamines in the presence of K2S2O8 and KOt-Bu in DMSO–H2O afforded the desired 2-arylbenzothiazoles in good yields. It is notable that no transition-metal catalyst is needed in this reaction. Compared with other known methods, this method of synthesizing 2-arylbenzothiazoles can be advantageous in cases where substituted benzothiazoles and benzylamines are readily available.
Keywords: 2-aryl benzothiazoles; benzylamines; K2S2O8; KOt-Bu; oxidative cyclization